Multiply x by each term in x^2-2x+4
Then multiply -1 by each term in x^2-2x+4.
Then add up all terms.
Then collect all the x^3, x^2, x and constant terms. For example, you should have two x^2 terms: -2x^2 and -x^2. Combine them and write them as -3x^2.
(2+i)(2-i) = 4 - i^2 = 4 - (-1) = ?
Multiply (x-1)(x^2-2x+4)
Simplify (2+i)(2-i)
2 answers
Just to see if I calculated correctly the first problem = x^3-3x^2+6x-4.
Then the answer to the other problem is 5.
Then the answer to the other problem is 5.